Pelatihan dan Pendampingan Implementasi Artificial Intelegence dalam Pembelajaran pada Lembaga Pendidikan Non-Formal - Anggawirya, Arin Mantara; Reliubun, Abdurrahman Shaleh; Giovani, Evelin; Istiqomah, Nurul; Floriani, Rosalia; Sijabat, Survey; Purwaningsih, Yuni Ratna (Universitas Pahlawan Tuanku Tambusai, 2026)
Non-formal educational institutions serve as one of the main pillars in achieving quality education. This community service program aims to disseminate integrating Artificial Intelligence (AI) in learning to enrich students’ educational experiences. The methods employed in this program include systematic training and mentoring, accompanied by questionnaires to measure participants’ improvement. Descriptive statistical analysis using mean analysis was conducted to examine the significance of changes that occurred. The results indicate a significant improvement across all measured aspects. Participants not only gained an understanding of basic AI concepts but also demonstrated the ability to utilize various AI platforms to support more creative and interactive learning abilities. Further mentoring strengthened teachers’ reflective abilities and ethical awareness in integrating AI in a balanced and purposeful manner. This program successfully enhanced digital literacy and pedagogical competence among educators in non-formal educational institutions. It demonstrates that continuous training and mentoring approaches can serve as an effective model for accelerating the digital transformation of education in the era of Artificial Intelligence.